2020
DOI: 10.1177/0194599819900487
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sleep Apnea and Cancer in Veterans

Abstract: Objective To test the association between preexisting obstructive sleep apnea (OSA) and subsequent cancer in a large long-term cohort of veteran patients. Study Design Retrospective matched cohort study. Setting The Veterans Affairs Health Care System. Subjects and Methods All veteran patients diagnosed with OSA between 1993 and 2013 by International Classification of Diseases, Ninth Revision ( ICD-9) codes in any Veterans Affairs facility and veteran patients without an OSA diagnosis, matched to patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 47 publications
2
66
0
1
Order By: Relevance
“…69,70 There is also evidence for a more than threefold increase in traffic accidents. 71 In addition, studies have reported increased risk of cancer, 18,72,73 metabolic disorders, 74,75 and all-cause mortality. 17 The physiological pathways between OSA and its negative consequences are complex and not fully understood.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…69,70 There is also evidence for a more than threefold increase in traffic accidents. 71 In addition, studies have reported increased risk of cancer, 18,72,73 metabolic disorders, 74,75 and all-cause mortality. 17 The physiological pathways between OSA and its negative consequences are complex and not fully understood.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Additionally, the co-occurrence of OSA and PTSD is more likely associated with increased PTSD symptoms severity [13]. Left untreated, OSA can lead to the development of serious chronic medical conditions such as type 2 diabetes, cardiovascular disease, stroke, hypertension heart failure, dementia, and certain type of cancers [7,14,15], thus further aggravating preexisting PTSD. Untreated OSA can also lead to neurocognitive deficits and the development of other psychiatric disorders and substance abuse which can lead to worsening severity of PTSD symptoms [16,17].…”
Section: Table 2: Dsm-5 Ptsd Diagnostic Criteriamentioning
confidence: 99%
“…Overall, eight cohort studies with 1 398 113 women were included in this meta-analysis. [17][18][19][20][21][22][23][24] Characteristics of the included studies were shown in Table 1. These studies were published from 2014 to 2021 and performed in the United States, 19,20,22,23 Canada, 24 China 17,18 and Korea.…”
Section: Studycharacteristicsandqualityevaluationmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Characteristics of the included studies were shown in Table 1. These studies were published from 2014 to 2021 and performed in the United States, 19,20,22,23 Canada, 24 China 17,18 and Korea. 21 Regarding study design, three of them were prospective cohort studies, 17,19,23 while the other five were retrospective studies.…”
Section: Studycharacteristicsandqualityevaluationmentioning
confidence: 99%